PERCEPATAN PEMBERDAYAAN EKONOMI DESA KALIREJO MAGELANG BERBASIS SDG’S: EKSKALASI PRODUK OLAHAN UMKM - Sitoresmi, Mumpuni Wahyudiarti; Nurmala Dyah Fajarningrum; Destri Tsurayya Istiqamah; Emmaculata Sac Cid Ananda; Ega Friska Fadilla (STMIK Royal, 2025)
Abstract: This community engagement project seeks to improve the efficiency and effectiveness of processed product development by Micro, Small, and Medium Enterprises (MSMEs) in Kalirejo Village, Magelang Regency. The village is home to various MSMEs producing household food items such as grubi, slondok, etawa goat milk, honey, and other culinary goods. The predominant issues faced by these MSMEs include limited promotional outreach, inadequate marketing strategies, weak branding, and inefficient packaging and distribution systems, all of which hinder community income. Utilizing a Participatory Action Research (PAR) approach, the program provides intensive guidance to MSME actors in enhancing product development, branding, packaging, and digital marketing. The program also supports MSMEs in obtaining legal business documentation, including Business Identification Numbers (NIB), Trade Business Permits (SIUP), and Halal Certification from MUI. The anticipated outcomes include improved product quality and diversity, increased marketing efficiency, broader customer reach through social media, and a higher number of MSMEs with official business permits. Keywords: SDGs; MSMEs; business legality; product escalation. Abstrak: Program pengabdian ini bertujuan untuk meningkatkan kualitas serta efisiensi pengolahan produk Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Kalirejo, Kabupaten Magelang. UMKM di wilayah ini memproduksi beragam makanan rumahan seperti grubi, slondok, susu kambing etawa, madu, dan aneka pangan lainnya. Kendala utama yang dihadapi para pelaku usaha adalah kurang optimalnya promosi, strategi pemasaran yang belum efektif, lemahnya branding, serta kemasan dan distribusi yang belum memadai, yang berdampak pada pendapatan masyarakat. Melalui pendekatan Participatory Action Research (PAR) meliputi perencanaan, tindakan, observasi, dan evaluasi, kegiatan ini memberikan pendampingan intensif dalam aspek pengolahan produk, desain kemasan, branding, serta pemasaran berbasis digital. Selain itu, program ini juga mendukung pengurusan legalitas usaha seperti Nomor Induk Berusaha (NIB), Surat Izin Usaha Perdagangan (SIUP), dan Sertifikat Halal dari MUI. Hasil yang diharapkan adalah peningkatan kualitas produk, jangkauan pemasaran yang lebih luas melalui media sosial, serta bertambahnya jumlah UMKM yang memiliki legalitas resmi. Kata kunci: SDGs; UMKM; legalitas usaha; ekskalasi produk.